Necesidad y azar en el imperio. Fiscalidad, vínculos locales y mediación en ciudades de la monarquía de España, 1592-1634 - Bautista y Lugo, Gibran Irving Israel (Anuario de Historia de América Latina, 2020)
The article compares cases of tax negotiation in Quito, Oporto, Burgos, Mexico and Naples during the union of Iberian crowns. The role of mediators between the royal demands for fiscal resources and the response of the cities is emphasized; individuals whose agendas and interests articulated the local sphere of the cities where they operated and the trans-imperial dimension of the monarchy. The conditions of the mediation outlined the collection, which transformed the extraordinary services requested by the Crown into ordinary local taxation, as well as the participation of private agents in the benefits. It is argued that the mediation dynamics fostered the stakeholders’ confluence and their interaction at various scales. Beyond the governmental or corporate instruments used in each specific negotiation, the mediators’ action determined the configuration of the monarchy.